Azimuth and elevation factors correction for single station lightning electromagnetic field sensor - S A Mohammad,; M R Ahmad,; M Abdullah,; S A S Baharin,; Park, S J; Cooray, V (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to find the location of lightning return strokes using a single station electromagnetic field sensor with the implementation of magnetic field Factor B correction to best match with a reliable lightning strike location reference from TNB Research (TNBR) that uses Vaisala lightning detector with ±500m tolerance. A parallel plate antenna was used to measure the electric fields while two orthogonal loop antennas were used to measure the magnetic fields from thunderstorms in Melaka. Based on the type of Cloud-to-Ground flash and its recorded magnetic field peak amplitude polarities, the general direction of the lightning source could be determined in four quadrants divided equally between the cardinal directions. Measurement of return stroke peak amplitudes from electromagnetic field waveforms, distance between lightning measurement station and lightning strike was determined. Factor B corrections varied between 53M to 69M where the separation distance between compared strikes averaged 3.22 km. From the varied Factor B, it was averaged to 60.1M that yield a separation distance between the same compared strikes between 0.75 to 15.02 km. From all the strikes compared, the average separation distance between compared strikes was 7.64 km. It was determined that the accuracy of our lightning measurement system lightning location were between 7.14 and 8.14 km.